The concepts of planning and design in sustainable stormwater management - Tukiman, Izawati; Zen, Ismawi; Musa, Mohd Faiz (WIT Press, 2015)
Stormwater management requires general ideas and principles known as the “concept” to ensure the success of planning and design. In addition, the concept requires an understanding of the hydrology cycle as a basis of knowledge, which provides a mechanism to synthesize the knowledge of the hydrology cycle with the idea of planning and designing for stormwater management. Thus, this research aims to synthesize the concepts of stormwater management with that of the hydrology cycle as the environmental sustainability factor. Two objectives have been established: (i) to identify the concepts of planning and designing of stormwater management; and (ii) to analyse the relationship of the identified concepts with the hydrology cycle. In this qualitative research, three methods of data collection have been used: online journals, forum discussions and e-mail interviews. The collected data were analysed using five steps of descriptive comparative analysis. The results show eleven concepts: conservation of the watershed, compact urban form, retention of stormwater on site, treatment train, green network, harvesting and reuse of rainwater, redevelopment, streetscape ecosystem and restoration. The concepts are listed according to seven hydrology cycles – interception, infiltration, surface runoff, depression storage, evapotranspiration, groundwater flow and interflow. The hydrology cycle becomes the environmental sustainability factor for the identified concepts, as the goal of stormwater management is to replicate the process of the hydrology cycle to ensure the effectiveness of the concepts.